Pengayaan Keterampilan Pembangunan Perahu Kecil Fiberglass untuk Sarana Produksi Usaha Mikro Budidaya Rumput Laut di Kabupaten Jeneponto - Wahyuddin Mustafa; Syamsul Asri; Farianto Fachruddin; Syarifuddin Dewa; Lukman Bochary; Ganding Sitepu; Rosmani -; Wihdat Djafar; A. Ardianti; Moh. Rizal Firmansyah (Faculty of Engineering UNHAS, 2019)
Generally, people who live along the coast of Jeneponto regency do the seaweed cultivation both in group or in person. One of the group is Pattontongan city group in the area of Pattontongan, Binamu subdistrict. They used both wooden boat and FRP boat for the activities. Of the latter, they got their FRP boat from the Indonesian government as it to expensive to buy them in person. In order to maintain their FRP boat, a training for repairing their FRP boat have been conducted by the team of lecturers from the Departmen of Naval Architecture Engineering Faculty, Unhas for the group. To improve their skills, a further training have been conducted recently as well. The training focus on how to build the FRP boat from beginning. The result of the training shows that the participants which are the seaweed farmers are being able to 1) read a boat design, 2) transfer the boat design into full scale design, 3) make the boat mould, 4) layering the boat using hand lay-up method. By being able to do all those activities, the seaweed farmers have improved their skills of making the FRP boat. The skills have opened an opportunity for the seaweed farmers to increase their well being by getting an order of repairing and building FRP boat.